2016
DOI: 10.1007/s40974-016-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the ecology of tree-seedling growth in dry tropical environment: a management perspective

Abstract: The dry tropical forests are among the most vulnerable ecosystems of the world and, however, are relatively understudied. These forests provide various ecosystem services, and are progressively being converted into patches of dry scrubs, savanna and marginal cropland systems, due to various anthropogenic perturbations. Soils of these regions are relatively nutrient poor with a patchy nutrient and water distribution pattern. Therefore, the variability in these natural resources imposed by the present climate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 160 publications
(202 reference statements)
0
19
0
1
Order By: Relevance
“…Amount of light available on the forest floor has been reported as a strategic environmental regulator which governs intrinsic growth behavior of residing plant species (Augspurger 1984;Walters and Reich 1996;Bhadouria et al 2018). Heterogeneity in the availability of light in a forest is associated with morphological and physiological adaptations, and therefore directly determines the species composition at community level (Lüttge et al 2002;Bhadouria et al 2016Bhadouria et al , 2017a. Valladares and Niinemets (2008) suggested that the understanding of species-specific response to acclimatize and grow in low-light environments will help in the assessment of ecosystem responses to global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Amount of light available on the forest floor has been reported as a strategic environmental regulator which governs intrinsic growth behavior of residing plant species (Augspurger 1984;Walters and Reich 1996;Bhadouria et al 2018). Heterogeneity in the availability of light in a forest is associated with morphological and physiological adaptations, and therefore directly determines the species composition at community level (Lüttge et al 2002;Bhadouria et al 2016Bhadouria et al , 2017a. Valladares and Niinemets (2008) suggested that the understanding of species-specific response to acclimatize and grow in low-light environments will help in the assessment of ecosystem responses to global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged drought periods may favor increased similarity between strata of woody vegetation, as humidity is an important filter for less rustic seedlings [51], [52], [18], especially for species with wide variation of phenological behavior and for those with low abundance of individuals in the adult stratum, resulting in interannual variation of seed production and germination and, consequently, of individuals able to be recruited.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, seedling source plays a key role in the viability of planting material and is often overlooked in tree planting campaigns [28]. This is because seedling stage is considered the most sensitive stage in the lifecycle of trees and seedling care from early establishment is critical to survival [35,46]. Tree seedlings distributed to farmers were sourced from different nurseries across the study sites due to the large number of seedlings required and the structure of nursery enterprises in the area, that is, most nurseries are smallholder owned and run.…”
Section: Discussionmentioning
confidence: 99%